1982
DOI: 10.1021/ac00251a025
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of liquid junction potentials for equilibrium studies

Abstract: A detalled conslderatlon of the assumptlons underlylng the Henderson equatlon Indicates that, contrary to wldely held vlews, the ciilculatlon of llquld junctlon potentlals vla thls equatlon Is rellable under certaln well-deflned condltlons. I n particular thls Is shown to be true for the constant lonlc strength llquld junctions commonly used In equlllbrlum studles. The valldlty of the potentials calculated from the Henderson equatlon Is demonstrated dlrectly by comparlson of the calculated potentials wlth "exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 24 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…As recognized by Xiao et al (2002), extrapolation of such data to infinite dilution depends strongly on the activity coefficient model adopted. In addition, the correction for liquid junction (diffusion) potentials is always problematic (Hefter, 1982) and, again as noted by Xiao et al (2002), their result is higher than those reported by most other researchers.…”
mentioning
confidence: 73%
“…As recognized by Xiao et al (2002), extrapolation of such data to infinite dilution depends strongly on the activity coefficient model adopted. In addition, the correction for liquid junction (diffusion) potentials is always problematic (Hefter, 1982) and, again as noted by Xiao et al (2002), their result is higher than those reported by most other researchers.…”
mentioning
confidence: 73%
“…The liquid junction potentials at this high ionic strength salt bridge are assumed to be negligible in the range 2 < pH < 11 [24]. In all potentiometric measurements, the electrodes were calibrated before and after each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…For constant ionic medium junctions, Ej can be deter mined experimentally or, as in the pertinent case, cal culated by an approximate form of the Henderson equation (3) [6,7]; the limiting ionic conductivities Ag were taken from [8]. The e.m.f.…”
Section: Methodsmentioning
confidence: 99%